The Most rapid recurrent meningioma: Case report and literature review. (March 2023) - Adji, Novan Krisno; Putri, Komang Yunita Wiryaning; Indreswari, Laksmi; Nugraha, Muhammad Yuda; Habibi, Ali
Abstract: Introduction: Meningioma, a primary intracranial neoplasm, accounts for 36 % of all primary brain tumors. Approximately 90 % of cases are benign. Malignant, atypical and anaplastic meningioma potentially have more recurrence risk. In this paper, we report a rapid recurrence of meningioma that is probably the most rapid recurrence for either benign or malignant type. Case presentation: This paper reports a case of rapid meningioma recurrence 38 days after the first surgical resection. The histopathological examination showed suspicion of anaplastic meningioma (WHO grade III). The patient has a history of breast cancer. After total surgical resection, there was no recurrence reported until three months, and the patient was planned for radiotherapy. Only several cases have been reported about the recurrence of meningioma. With recurrence the prognosis is poor, and two patients died several days after treatment. The primary treatment for the entire tumor was surgical resection, and several issues were combined with radiotherapy. In this case, the recurrence time from the first surgery was 38 days. The most rapid recurrent meningioma reported to this day was 43 days. Conclusion: This case report showed the most rapid onset of recurrent meningioma. Therefore this study cannot show reasons for the rapid onset of recurrence. Highlights: Rapid recurrence of meningioma in 38 days after first surgical resection. The most rapid onset of recurrence in meningioma Malignant meningioma Possibility due to breast cancer history of patient